Prediction of Domino Pizza Customer Service Quality Level in Tangerang Area using Heteroscedasticity Purchase Satisfaction Test using Sampling Method - Tapawinaka, Gusti Agung Gede (JURNAL SISFOTEK GLOBAL, 2025)
Pizza is one of the Italian foods that is a favorite menu in various parts of the world. In Indonesia itself, we can more easily find pizza variants spread across various regions in Indonesia. We just have to choose according to taste. The pizza that is the object of the study is some that come from original Italian recipes, some that adopt typical Indonesian. The pizza that is the object of the study is Domino's Pizza. The purpose of this study is to determine the effect of Instagram influencer endorsement on pizza purchasing decisions, which focuses on product factors, price factors, promotion factors, place factors and influencer factors. The product, price, promotion, place and influencer variables are independent variables and the purchasing decision variable is the dependent variable, so that the calculation carried out by the sampling method can be appropriate. The study was conducted on consumers in the Tangerang area using the sampling method. The use of datasets in this study was carried out with a quantitative approach. Data collection was carried out by collecting online questionnaires filled out by pizza consumers. The independent variables of the study are product (X1), price (X2), promotion (X3) and place (X4). As a moderating variable, namely Instagram influencer endorsement (Y) on purchase satisfaction (Z), this is the data collection that will be processed later. In this study, the questionnaire will be tested with validity and reliability tests. Then classical testing is carried out, hypothesis testing with the F test and t test.